2003
DOI: 10.1111/j.1567-1364.2003.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the salt-tolerant yeastZygosaccharomyces rouxiiin microtiter plates: effects of NaCl, pH and temperature on growth and fusel alcohol production from branched-chain amino acids

Abstract: Zygosaccharomyces rouxii, a salt-tolerant yeast isolated from the soy sauce process, produces fusel alcohols (isoamyl alcohol, active amyl alcohol and isobutyl alcohol) from branched-chain amino acids (leucine, isoleucine and valine, respectively) via the Ehrlich pathway. Using a high-throughput screening approach in microtiter plates, we have studied the effects of pH, temperature and salt concentration on growth of Z. rouxii and formation of fusel alcohols from branched-chain amino acids. Application of mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…García et al [42], reported the tolerance of S. pombe to pH 3, under aerobic and anaerobic conditions, in which the yeast exceeded a survival of about 80%, similarly to what was observed in our study. Jansen et al [57] studied the behavior and growth of Z. rouxii under different pH values (ranging from three to seven), reporting that the yeast can maintain optimal growth and metabolite production even at the lowest pH values, which are in agreement to what was observed for the isolate studied here. In the case of R. ruineniae, Boro and Narzary [48] reported that the yeast is able to grow at a pH range of two to eight.…”
Section: Survival At Low Ph and Growth At 37 • Csupporting
confidence: 88%
“…García et al [42], reported the tolerance of S. pombe to pH 3, under aerobic and anaerobic conditions, in which the yeast exceeded a survival of about 80%, similarly to what was observed in our study. Jansen et al [57] studied the behavior and growth of Z. rouxii under different pH values (ranging from three to seven), reporting that the yeast can maintain optimal growth and metabolite production even at the lowest pH values, which are in agreement to what was observed for the isolate studied here. In the case of R. ruineniae, Boro and Narzary [48] reported that the yeast is able to grow at a pH range of two to eight.…”
Section: Survival At Low Ph and Growth At 37 • Csupporting
confidence: 88%
“…The Ehrlich's reaction is based on two steps: firstly, a transamination reaction in which the amino group from the amino acid is transferred to an α-ketoglutarate to form an α-keto acid and glutamate [50,54]. Secondly, α-keto acid is decarboxylated into an aldehyde [55] and then finally due to redox status of the yeast cell, the aldehyde can be reduced to its respective higher alcohol or can be oxidised into a volatile carboxylic acid. The ability to produce higher alcohols is strictly strain-dependent, and this feature can be used as a determining character in yeast selection for industrial purposes [19,21].…”
Section: The Main Chemical Categories Behind Wine Aromamentioning
confidence: 99%
“…26, x FOR PEERREVIEW 10 of 20 which can be present in wines are ethyl mercaptan (EtSH), dimethyl sulphide (DMS, grassy/truffle-like), diethyl sulphide (DES), dimethyl disulphide (DMDS), diethyl disulphide (DEDS), methyl thioacetate (MTA), ethyl thioacetate (ETA), 2-mercaptoethanol (ME), 2-(methylthio)-1-ethanol (MTE), 3-(methylthio)-1-propanol (MTP), 4-(methylthio)-1-butanol (MTB, earthy-like scent), benzothiazole (BT) and 5-(2-hydroxyethyl)-4-methylthiazole (HMT). DMS, MTB, MTE and BT are characteristic of Merlot wines[55].…”
mentioning
confidence: 98%
“…Therefore, stress conditions including NaCl (120 g/L), heat shock (5 min at 56 °C), glucose The salt content in high-salt liquid fermentation sauce mash is high, so the salt tolerance of added strain is very strict [33][34][35]. Yeast Zygosaccharomyces rouxii and T. globosa are commonly used in soy sauce fermentation [36][37][38][39]. Therefore, the tolerance performance of mutant HF-130 was test and compared with yeast Zygosaccharomyces rouxii, T. globosa, and AY12a.…”
Section: Growth Tolerance and Fermentation Performance Of Hf-130mentioning
confidence: 99%